1999
DOI: 10.1002/(sici)1097-4636(1999)48:2<121::aid-jbm5>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Effect of porosity and environment on the mechanical behavior of acrylic bone cement modified with acrylonitrile-butadiene-styrene particles: I. Fracture toughness

Abstract: The elastomeric copolymer acrylonitrile-butadiene-styrene (ABS) was added to a conventional acrylic bone cement matrix. The results obtained show that although strength and stiffness decreased with an increasing second phase volume fraction, ductility and toughness both increased. The crack propagation became stable for specimens containing over a 5% volume fraction of the second phase. The fracture toughness increased up to 60% when the amount of ABS reached 20% (v/v). For larger amounts linear elastic fractu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…On the one hand, the interest for injectable self-setting materials, which have a great potential on the field or minimally invasive surgical techniques, has led to the development of calcium phosphate cements. Traditionally, the bone cements used in orthopaedics have been polymer based [5][6][7]. However, during the early 1980s, the idea of developing calcium phosphatebased cements was put forward by LeGeros et al [8] and was further investigated by Brown and Chow [9].…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, the interest for injectable self-setting materials, which have a great potential on the field or minimally invasive surgical techniques, has led to the development of calcium phosphate cements. Traditionally, the bone cements used in orthopaedics have been polymer based [5][6][7]. However, during the early 1980s, the idea of developing calcium phosphatebased cements was put forward by LeGeros et al [8] and was further investigated by Brown and Chow [9].…”
Section: Introductionmentioning
confidence: 99%
“…Although significant improvement on the mechanical properties is possible through the incorporation of fiber-reinforcing phases, [11][12][13][14] previous studies have shown that the flow characteristics of the resultant composite are severely compromised. This has led to studies of particulate-filled composite bone cements [15][16][17][18][19][20][21][22][23][24] that offer the possibility of improved mechanical properties without severe reductions in flow characteristics of the precured polymers. The present investigation explored this approach through the incorporation of glass particles within a bone cement.…”
Section: Introductionmentioning
confidence: 99%
“…Highly viscous initial mix results in both poor workability of the paste and high porosity of the hardened material. From the analysis of the results reported by previous workers, it emerges that some authors incorporated the filler maintaining the L/P ratio equal to 0.5, [15][16][17][18] while others prepared composite cements by replacing part of the PMMA powder by the filler. 19 -22 The latter method allows the addition of a higher amount of filler without jeopardizing the workability of the cement.…”
Section: Introductionmentioning
confidence: 99%
“…The absence of AE signals in the reference formulation (bone cement without core-shell nanoparticles)does not imply the inexistence of damage signs in the material Liu et al (2001). reported that the bone cements subjected to a compressive load undergo yield but they do not break or fracture; authors also observed "yield crack bands" crossing the transverse section of the yield specimens.The fact that the presence of particles induces some effect in cements when these are subjected to external forces is not unusual;Vila et al (1999) studied the influence of mixing the elastomeric acrylonitrile-butadiene-styrene (ABS) copolymer into a bone cement matrix on the mechanical properties and concluded that rubber particles have a double effect in the failure of cements. On the one hand, the elastomeric particles are additional nucleation sites for crazes or microcracks which extend from the damage zone while, on the other hand, the elastomeric particles can also hinder the craze or microcrack…”
mentioning
confidence: 99%